2018
DOI: 10.1111/risa.13234
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Climate Change as an Emerging Risk to Infrastructure Systems

Abstract: The consequences that climate change could have on infrastructure systems are potentially severe but highly uncertain. This should make risk analysis a natural framework for climate adaptation in infrastructure systems. However, many aspects of climate change, such as weak background knowledge and societal controversy, make it an emerging risk where traditional approaches for risk assessment and management cannot be confidently employed. A number of research developments aimed at addressing these issues have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 59 publications
(61 reference statements)
0
12
0
1
Order By: Relevance
“…In particular, one of the primary factors motivating the development of RDM was the observation that in multi-stakeholder climate change contexts, probabilistic characterizations of uncertainty are likely to be subject to contention and bias (Lempert et al, 2006;Lempert, Nakicenovic, Sarewitz, & Schlesinger, 2004). Previous research has also demonstrated that climate change experts may be resistant to probabilistic characterizations of their beliefs (Arnell, Tompkins, & Adger, 2005;Vaughan & Spouge, 2002), and that these beliefs and areas of expertise may not be well matched to adaptation needs (Shortridge & Camp, 2019). Thus, it may be reasonable to base exploratory sampling on distributions that may actually deviate from expert beliefs if they better support the goals of RDFs; namely, to identify robust strategies and characterize vulnerabilities.…”
Section: Uniform Normalmentioning
confidence: 99%
“…In particular, one of the primary factors motivating the development of RDM was the observation that in multi-stakeholder climate change contexts, probabilistic characterizations of uncertainty are likely to be subject to contention and bias (Lempert et al, 2006;Lempert, Nakicenovic, Sarewitz, & Schlesinger, 2004). Previous research has also demonstrated that climate change experts may be resistant to probabilistic characterizations of their beliefs (Arnell, Tompkins, & Adger, 2005;Vaughan & Spouge, 2002), and that these beliefs and areas of expertise may not be well matched to adaptation needs (Shortridge & Camp, 2019). Thus, it may be reasonable to base exploratory sampling on distributions that may actually deviate from expert beliefs if they better support the goals of RDFs; namely, to identify robust strategies and characterize vulnerabilities.…”
Section: Uniform Normalmentioning
confidence: 99%
“…Weather and environment-related variables are not as common as the previously mentioned variables. This is an important shortcoming of the previous studies as it is well established that the management and assessment of infrastructure risk usually rely on climate-related historical data (Shortridge & Camp, 2019). The most common variables in this category are soil type, humidity, temperature, and precipitation.…”
Section: Type Of Explanatory Variables Usedmentioning
confidence: 99%
“…Effective regional adaptation strategies typically involve extensive planning, large investments, and persuasion of vulnerable residents through outreach and education. Extensive modeling must precede implementation of strategies and, for the models to be trusted, they must be exhaustively tested against data and results must be communicated appropriately [71]. Different regions and agencies use differing modeling capabilities to forecast severe weather and ocean events.…”
Section: Strategies For Adapting To Future Flooding Land Loss and Health Threatsmentioning
confidence: 99%